Capital investment incentives in an inflationary environment - R. C. Doenges; W. D. Hamman (South African Journal of Business Management, 1983)
The attention in this paper has been directed at the problem whether the 30% machinery investment allowance was sufficiently high enough seen against the background of the present double digit inflation. The authors arrived at the interesting conclusion that the shortfall at replacement is caused by the fact that depreciation for fiscal purposes is based upon historical cost and not on replacement cost. The investment allowance filled this gap and it was concluded that this allowance was high enough in the majority of cases.
Keywords: 650